Stages Of Formation Of Illustrative Thinking (Journal of Pedagogical Inventions and Practices, 2025)
This article broadly covers the essence of the concept of figurative thinking, its role in the types of thinking and its specific features. Figurative thinking directly affects a person's creative thinking, the formation of aesthetic taste and the expression of his emotional world. The article presents analytical ideas about the forms of expression of figurative thinking in literature, art and other cultural spheres, its differences from logical thinking, as well as its importance in the development of human thinking. The study reveals the possibilities of a deep understanding of figurative thinking and its effective application in creative activity